Identifikasi Nilai Pendidikan Karakter di dalam Permainan Tradisional Pehe - P Lejap, Gracianus Edwin Tue; Demon, Yohanes (Universitas Mathla'ul Anwar Banten, 2023)
Character education is the basis for forming new characters that are always oriented towards the welfare of life. This research aims to explore and introduce various character values in the traditional pehe game. The research method used is literature study. The results of the research show that the traditional pehe game contains several character education values, including the value of cooperation, the value of creativity, the value of responsibility, the value of honesty and the value of communicativeness. These values provide an important illustration that traditional games will remain a valuable asset in forming strong characters in students